Lecturing with Animations on the Measuring Experiment for the Mechanical Equivalent of the Heat - Nigmet KOKLU; Dundar Yener; Hamdi Sukru KILIÇ (International Journal of Applied Methods in Electronics and Computers, 2017)
In this study, animations were used to get for students to better and easier undertand to comprehend the topic of "measurement of the mechanical equivalent of the heat," described and conducted in the general physics laboratory. The descriptions related to the experiment and the topic were composed in the form of animation. The measuring solution of the mechanical equivalent of the structure and heat of the calorimeter was presented also by animations. Thus, it is desirable to provide students with an entertaining opportunity to learn more about the topic as well as to keep alive the interest of the students all the way. The materials along with their shapes to be used in the comparison experiment of the specific heats were shown as animations. The animation communicates with you in which steps should be followed in order to conduct the experiments properly. Additionally, the related literature on conceptual errors has been investigated in order to prevent possible misconceptions about this topic. In this way, it is aimed that the students will comprehend the experiment more easily.